Isu-Isu Permasalahan Dalam Penelitian PAI - Khairunnida Kusmianto; Nuril Huda (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Research in Islamic Religious Education (PAI) faces dynamic challenges alongside the changes in the era of globalization and the post-pandemic period. This article aims to map the characteristics of qualitative and quantitative research methodologies and identify crucial issues in PAI during the 2020–2025 period. Through literature analysis, it was found that qualitative research is highly relevant for exploring deep meanings of religious practices, while quantitative research is necessary to test the effectiveness of learning models. Key issues identified include the impact of online learning, the moral degradation of the younger generation, intolerance, and the challenges of teacher competence in the digital era. The results of the study conclude that PAI requires an adaptive and solutive research approach to maintain the relevance of religious values amidst modernity. Additionally, external factors such as the impact of post-pandemic online learning, moral degradation, and radicalism further complicate PAI challenges in the digital era. The study concludes that comprehensive reform is needed in the planning, implementation, and evaluation of learning, supported by appropriate research methodologies to maintain the relevance of PAI as a strategic instrument for developing a generation with noble character.